Política cultural no RN: uma avaliação das casas de cultura popular (2003/2010) - Silva, Jóis Alberto da (2012)
The issue of public policy for the culture area has experienced a significant increase of interest of academic researchers. The research "Cultural Policy in infants: an evaluation of the home culture (2003/2010)" aimed to evaluate the effectiveness of cultural policy in Rio Grande do Norte in the period 2003/2010. When was the program created and deployed the houses of popular culture. Specifically, he sought: a) mapping the major elements of cultural policy in the RN during the chronological period mentioned b) hold up in more detail in the description of the implementation process of the houses of popular culture, c) investigate cultural actions implemented by the houses of popular culture and its effectiveness. The methodological process consisted of a review of the literature on culture, cultural policy, public policy and public policy evaluation for the construction of the theoretical-analytical, documentary research in public and private institutions related cultural production; interview with managers and cultural producers in visits field research conducted in seven major houses of popular culture, taken as a sample of the total d 29 outlets installed during the chronological period mentioned. The survey found that the program houses RN popular culture in general was effective in meeting its objectives, among which the decentralization of cultural inclusion in the artist market cultural production, the promotion of folk traditions in the region , respect and support for new artists, respect and support for popular memory